Kuala Kedah Marine and Maritime Center, Kuala Kedah, Kedah - Muhammad Khairi Ismail
The vision of the new Kuala Kedah Marine/Maritime Center (KKMMC) is a campus where traditional boundaries between departments are replaced by a spirit of collaboration; a campus designed in such a way that scientist and students may meet spontaneously with engineers and locals to envision new technologies and research that improve marine and maritime industry in their everydaylife; a campus that is open and welcoming the public. It should be designed to be a landmark, a place people will want to visit, allowing the Institute to reach out to the surrounding community and internationally. The new KKMMC should be a flexible and dynamic sanctuary for everyone in search of knowledge, inspiration and personal development. An open and accessible learning environment by providing space for contemplation, knowledge and just plain being. KKMMC prioritizes networking and cooperation. A variety of institution and companies can be involved in the network organization of the institute and contribute knowledge and inspiration. Users will be involved throughout the process, and further knowledge and know-how will be gathered from international cultureal and knowledge institution.